1980
DOI: 10.1038/bjc.1980.333
|View full text |Cite
|
Sign up to set email alerts
|

Faecal bile acids and clostridia in patients with breast cancer

Abstract: Summary.-We have studied 30 patients presenting with breast cancer and 36 control patients admitted to hospital for minor surgery. Stool specimens were obtained for bile acid analysis and bacterial nuclear dehydrogenation activity (NDC) estimation.The mean total faecal bile acid (FBA) concentration (,tmol/g) in patients with breast cancer was 15-6 + 1-8 s.e., significantly lower than for control patients (20.5 + 1-9).NDC were isolated from the faeces of 58% of breast cancer patients and 15% of control patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Reddy et al, (1998) found the intake of starch and dietary fibre to be negatively associated with the faecal concentration of DCA and faecal pH. Several studies have reported differences in faecal bile acids excretion or in the composition of the major faecal bile acids in breast cancer patients (Murray et al, 1980;Papatestas et al, 1982;Owen et al, 1986), but the results have been equivocal. However, these studies can be criticised as the disease process or treatment may have affected liver function.…”
Section: Introductionmentioning
confidence: 99%
“…Reddy et al, (1998) found the intake of starch and dietary fibre to be negatively associated with the faecal concentration of DCA and faecal pH. Several studies have reported differences in faecal bile acids excretion or in the composition of the major faecal bile acids in breast cancer patients (Murray et al, 1980;Papatestas et al, 1982;Owen et al, 1986), but the results have been equivocal. However, these studies can be criticised as the disease process or treatment may have affected liver function.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that rates of breast and colon cancers are highly correlated with each other and with high fat and animal protein diets (Drasar & Irving, 1973). In the few studies published the data suggest that women with breast cancer may have differences in the faecal excretion of bile acids compared with controls; decreased (Murray et al, 1980) and increased (Papatestas et al, 1982) faecal concentrations, and altered ratio of individual bile acids (Owen et al, 1986) have been reported. Long-term follow-up of women undergoing cholecystectomy has revealed an increased risk of breast cancer which increased with time after operation (Gudmundsson et al, 1989).…”
mentioning
confidence: 99%
“…Since Hill's original hypothesis linking bile acids and breast cancer (Hill et al, 1971), a number of studies have demonstrated differences in faecal bile acid excretion or in the composition of the major faecal bile acids in breast cancer patients (Murray et al, 1980;Papatestas et al, 1982;Miller et al, 1983;Owen et al, 1986). These findings are consistent with the observed correlations between the incidences of cancer of the breast and colon and dietary factors such as fat intake (Hill et al, 1971;Drasar & Irving, 1973;Miller & Bulbrook, 1980).…”
mentioning
confidence: 99%